General Dental Practitioners’ and Faculty Members’ Opinions about Continuing Dental Education Program in Kerman - N Navabie (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Continuing dental education program is recognized as a necessary measure for promoting and maintaining the level of knowledge and skill of dental graduates. The aim of this study was to determine the opinions of general dental practitioners and faculty members view about different aspects of these programs. METHODS: This qualitative study used focus groups of 35 general dentists (in seven groups) and 27 members of the dentistry faculty (in ten groups). After transcription of the entire discussions, content analysis was done by coding and categorizing the data. FINDINGS: The total codes extracted from faculty members were 44 and for general dentists were 43 codes so divided in three categories. There were 9 common codes between two groups after assessment of the contents. CONCLUSION: General dentist’s needs including operative dentistry, root canal therapy and dental prosthesis should be considered in planning of these programs for quality improvement and increasing the efficacy and effectiveness of them.